The Influence of Work Skills and Work Experience on Improving Employee Performance in the Product Creation Center at PT Adis Dimension Footwear in Tangerang Regency - Gunawan , Rizki; Yulandari, Sri (UJoST- Universal Journal of Science and Technology, 2025)
The purpose of this study is to determine the extent to which work ability and work experience influence the performance of employees in the Product Creation Center department at PT. Adis Dimension Footwear, Tangerang Regency.This research uses a descriptive quantitative method with a sample of 73 respondents. The problem phenomenon identified by the researcher is based on the results of a preliminary survey, which showed suboptimal outcomes related to a lack of experience and work-related skills. As a result, employees have not been able to meet the targets set by the organization. In addition, many employees have not yet mastered the tasks assigned to them due to insufficient work experience. This has led to difficulties in making sound decisions, and their work performance has not met the expectations of their superiors and colleagues. These issues have ultimately led to a decline in employee performance. Based on the results of the study, it can be concluded that both work ability and work experience variables, either partially or simultaneously, have a significant influence on the performance of employees in the Product Creation Center department at PT. Adis Dimension Footwear, Tangerang Regency.